The Nature and Amount of Information in Cash Flows and Accruals - Bernard, Victor L.; Stober, Thomas L. (The Accounting Review, 1989)
[Based on stock price behavior around the release of annual reports in 1981 and 1982, Wilson [1987] concludes that for a given amount of earnings, the market reacts more favorably the larger (smaller) are cash flows (current accruals). The goals of this paper are to assess the generality of Wilson's finding and to assess alternative economic arguments that would manifest themselves as a "preference" for cash flows over current accruals. For the overall period, 1977-1984, there is no evidence of the simple relation observed by Wilson in his two-quarter test period. We then examine progressively more contextual models of the implications of cash flows and accruals. These models are also unsuccessful in explaining stock price behavior around the release of detailed financial statements. We conclude that either (1) the security price reactions to the release of cash flow and accrual data in financial statements are too highly contextual to be modeled parsimoniously, or (2) important uncertainties about the contents of detailed financial statements are resolved prior to their public release.]